DBSA to improve the compatibility, solubility, and infusibility of cellulose nanowhiskers modified by polyaniline in reinforcing a natural rubber-based nanocomposite - Silva, Michael Jones [UNESP] (2019)
In this study, the authors evaluate the potential of the reinforcement of cellulose nanowhiskers coated with polyaniline-DBSA (CNW-PANiDB) in a natural rubber latex nanocomposite. For this purpose, cellulose nanowhiskers (CNWs) were obtained by acid hydrolysis and coated with polyaniline by in situ polymerization in an acidic medium using dodecylbenzenesulfonic acid (DBSA). The nanocomposites based on natural rubber (NR) reinforced with CNW-PANiDB were obtained by a casting/evaporation method. Sample characterization was performed by DC electrical conductivity, thermogravimetric analysis, strain–stress test, UV–Vis–NIR and field emission scanning electron microscope. The UV–Vis–NIR spectrum of the NR/CNW-PANiDB nanocomposite revealed three characteristic absorption peaks around 350, 425, and 830 nm, assigned to PANiDB in emeraldine salt form. The mechanical properties of the nanocomposite, such as Young’s modulus and tensile strength, were improved by increasing the amount of CNW-PANiDB. The electrical conductivity of the nanocomposite increased by seven orders of magnitude by adding 10 mass% of CNW-PANiDB. This result indicates that CNWs coated with polyaniline-DBSA are an excellent material for use as mechanical reinforcement and to improve electrical conductivity. Thus, NR/CNW-PANiDB nanocomposite films have potential to be used as anticorrosive, electrostatic discharge, electromagnetic interference shielding materials, transducers, and electroactive materials.